Salivary alpha-amylase and cortisol responsiveness following electrically stimulated physical stress in bipolar disorder patients - Tanaka Y; Maruyama Y; Ishitobi Y; Kawano A; Ando T; Ikeda R; Inoue A; Imanaga J; Okamoto S; Kanehisa M; Ninomiya T; Tsuru J; et al. (Neuropsychiatric Disease and Treatment, 2013)
Yoshihiro Tanaka, Yoshihiro Maruyama, Yoshinobu Ishitobi, Aimi Kawano, Tomoko Ando, Rie Ikeda, Ayako Inoue, Junko Imanaga, Shizuko Okamoto, Masayuki Kanehisa, Taiga Ninomiya, Jusen Tsuru, Jotaro Akiyoshi Department of Neuropsychiatry, Faculty of Medicine, Oita University, Hasama-Machi, Oita, Japan Background: Bipolar disorder (BP) is often associated with a change in hypothalamus–pituitary–adrenal axis function change due to chronic stress. Salivary α-amylase (sAA) levels increase in response to psychosocial stress and thus function as a marker of sympathoadrenal medullary system activity. However, sAA has been studied less often than salivary cortisol in BP patients. Method: We measured Profile of Mood States and State-Trait Anxiety Inventory scores, heart rate variability, and salivary cortisol levels during electrical stimulation stress in 25 BP patients and 22 healthy volunteers. Results: Tension–anxiety, depression–dejection, anger–hostility, fatigue, and confusion scores in BP patients significantly increased compared with those of the healthy controls. In contrast, the vigor scores of BP patients significantly decreased compared with those of the healthy controls. Significant difference in the sAA levels was observed between BP patients and healthy controls. sAA of female patients was significantly higher than that of female healthy controls, and sAA in male patients tended to be higher than that of male healthy controls. No difference in salivary cortisol was observed between BP patients and the healthy controls. Only three time points were measured before and after the electrical stimulation stress. Furthermore, sAA secretion by BP patients increased before and after electrical stimulation. Conclusion: These preliminary results suggest that sAA may be a useful biological marker for BP patients. Keywords: HPA axis, bipolar disorder, α-amylase, cortisol, SAM activity